LG Electronics Benelux B.V. Employee Retention Policy Improvement - Ryan Nathaniel Limantara (iBuss Management, 2020)
Employee retention demonstrates the company’s ability to keep on giving incentive for the talented employees to stay within the company.  In the last few years, the company is having difficulties in retaining talented employees. These difficulties in retaining talented employees could then lead to high employee-turnover rate. Thus, the purpose of this research is to develop a strategy as to how LG Electronics Benelux B.V. can retain talented/high-potential/high-performing employees for a longer period of time.The analysis of this research paper is conducted based on the literature review that has been conducted by the writer. Moreover, interviews have been conducted with the HR Business Partner to get the employer’s perspective regarding employee retention as well as with the employees to get the employees’ perspective.  Furthermore, the result of the interviews will be for the writer to devise the recommendations as to how the company can retain talented employees for a longer period of time.With that being said, the research, interviews, and analysis all have been conducted very well and have produced a total of eight recommendations based on different aspects of employee retention to ultimately improve the company’s employee retention policy.Keywords: Employee Retention Policy, Talented Employees, Employee-turnover, Employee Retention, Improvement